Fetal motion estimation from noninvasive cardiac signal recordings. (21st October 2016) - Biglari, Hadis; Sameni, Reza
Abstract: Fetal motility is a widely accepted indicator of the well-being of a fetus. In previous research, it has be shown that fetal motion (FM) is coherent with fetal heart rate accelerations and an indicator for active/rest cycles of the fetus. The most common approach for FM and fetal heart rate (FHR) assessment is by Doppler ultrasound (DUS). While DUS is the most common approach for studying the mechanical activities of the heart, noninvasive fetal electrocardiogram (ECG) and magnetocardiogram (MCG) recording and processing techniques have been considered as a possible competitor (or complement) for the DUS. In this study, a fully automatic and robust framework is proposed for the extraction, ranking and alignment of fetal QRS-complexes from noninvasive fetal ECG/MCG. Using notions from subspace tracking, two measures, namely the actogram and rotatogram, are defined for fetal motion tracking. The method is applied to four fetal ECG/MCG databases, including twin MCG recordings. By defining a novel measure of causality, it is shown that there is significant coherency and causal relationship between the actogram/rotatogram and FHR accelerations/decelerations. Using this measure, it is shown that in many cases, the actogram and rotatogram precede the FHR variations, which supports the idea of motion-induced FHR accelerations/decelerations for these cases and raises attention for the non-motion-induced FHR variations, which can be associated to the fetal central nervous system developments. The results of this study can lead to novel perspectives of the fetal sympathetic and parasympathetic brain systems and future requirements of fetal cardiac monitoring.